2017
DOI: 10.18203/2320-1770.ijrcog20174051
|View full text |Cite
|
Sign up to set email alerts
|

A study to evaluate and compare the expulsion and continuation rates of post placental insertion of Cu 375 and CuT 380A in Indian women at a premier hospital in New Delhi, India

Abstract: Background: The Study was planned to evaluate and compare the expulsion and continuation rates of post placental insertion of Cu 375 and CuT380A in Indian women at Safdarjung Hospital New Delhi, after approval was obtained from Institutional Ethical committee.Methods: Study group consisted of 300 women, divided into two groups: Group A and Group B. The data was analysed by using ‘student “t” test/ non-parametric ‘Wilcoxon Mann Whitney’ for quantitative variables to evaluate the safety, efficacy and acceptabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 15 publications
3
7
1
Order By: Relevance
“…The overall discontinuation rate following expulsions in the present study (5.0%) was less than the previously reported rate (13.0%) . The expulsion rate of 3.4% with TCu380Ag was also less than the 4.9% and 5.6% rates recorded for Nova‐T200 and Nova‐T380, respectively.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…The overall discontinuation rate following expulsions in the present study (5.0%) was less than the previously reported rate (13.0%) . The expulsion rate of 3.4% with TCu380Ag was also less than the 4.9% and 5.6% rates recorded for Nova‐T200 and Nova‐T380, respectively.…”
Section: Discussioncontrasting
confidence: 81%
“…The present study demonstrated that the 1‐year continuation rate for postpartum insertions (82.2%) was greater than that for interval (78.1%) and MTP (71.3%) insertions in both groups. Previous studies reported a higher 6‐month continuation rate for postpartum insertions (88.2%) versus interval insertions (81.8%) . Postpartum insertions are therefore acceptable despite the expulsion rate (6.0%).…”
Section: Discussionmentioning
confidence: 89%
“…Menorrhagia was reported by 7.33% (n=11) subjects in group "A" and 8.66% (n=13) subjects in group "B" at the end of 1 year follow up. This difference was not statistically significant (P>0.05) [12] .…”
Section: Similarity and Differences In Results And Conclusion In Relmentioning
confidence: 65%
“…Mean age of the study population was 24.99 ± 4.2 years. The study showed that in group "A" 12% (n=18) women and in group "B" 14% (n=21) subjects complained of post insertion bleeding/spotting per vaginum at 1 month of IUCD insertion [12] . Menorrhagia was reported by 7.33% (n=11) subjects in group "A" and 8.66% (n=13) subjects in group "B" at the end of 1 year follow up.…”
Section: Similarity and Differences In Results And Conclusion In Relmentioning
confidence: 97%
See 1 more Smart Citation